PENERAPAN METODE WATERFALL PADA PENGEMBANGAN SISTEM INFORMASI MONITORING PROSES BIMBINGAN SKRIPSI DI JURUSAN ILMU KOMPUTER UNIVERSITAS LAMPUNG - Eko Septiawan; Dwi Sakethi; Rico Andrian (Jurnal Pepadun, 2022)
The thesis is a compulsory task that must be completed by a student as a condition of graduation to obtain a bachelor's degree. The questionnaire of the thesis guidance process shows, there were students who experienced problems in the thesis guidance process. The thesis guidance process monitoring information system has previously been developed but is still in the prototype phase. This study aims to develop a system that can assist students in monitoring the status of thesis examination that is being carried out by supervisors as well as providing information about thesis guidance and the percentage of thesis guidance students passing. This research uses the waterfall method. The thesis guidance process monitoring information system will show announcements from supervisors, thesis progress status, and thesis draft checking information.